Comparison of clinical efficacy of 3D-printed artificial vertebral body and conventional titanium mesh cage in spinal reconstruction after total en bloc spondylectomy for spinal tumors: a systematic review and meta-analysis - Dong, Mingjie; Gao, Yingjie; Fan, Hao; Wang, Yushan; Lv, Jia; Bai, Junjun; Shao, Pengfei; Gao, Yu; Lv, Zhi; Feng, Yi (Frontiers in Oncology, 2024)
Propose: This meta-analysis aimed to determine whether 3D-printed artificial vertebral bodies (AVBs) have superior clinical efficacy compared to conventional titanium mesh cages (TMCs) for spinal reconstruction after total en bloc spondylectomy (TES) for spinal tumors.: Electronic databases, including PubMed, OVID, ScienceDirect, Embase, CINAHL, Web of Science, Cochrane Library, WANFANG, and CNKI, were searched to identify clinical trials investigating 3D-printed AVB versus conventional TMC from inception to August 2023. Data on the operation time, intraoperative blood loss, preoperative and postoperative visual analogue scale (VAS) scores, preoperative and postoperative Frankel classification of spinal cord injury, vertebral body subsidence, and early complications were collected from eligible studies for a meta-analysis. Data were analyzed using Review Manager 5.4 and Stata 14.0.Results: Nine studies assessing 374 patients were included. The results revealed significant differences between the 3D-printed AVB and conventional TMC groups with regard to operation time (P = 0.04), intraoperative blood loss (P = 0.004), postoperative VAS score (P = 0.02), vertebral body subsidence (P < 0.0001), and early complications (P = 0.02). Conversely, the remaining preoperative VAS score and Frankel classifications (pre-and postoperative) did not differ significantly between the groups.The 3D-printed AVB in spinal reconstruction after TES for spinal tumors has the advantages of a short operative time, little intraoperative blood loss, weak postoperative pain, low This is a provisional file, not the final typeset article occurrence of vertebral body subsidence and early complications, and a significant curative effect. This could provide a strong basis for physicians to make clinical decisions.